National Laws and Regulations on the Prevention and Suppression of International Terrorism: Part II (M-Z) - United Nations (United Nations, 2005)
This volume, prepared by the Division for the Development and Codification of International Law of the Legal Department of the Secretariat of the United Nations, is the twenty-fourth in the United Nations Legislative Series, a systematic collection of those national legislative texts which deal with matters of international concern and constitute evidence of the practice of States in the field of international law. The purpose of this series is to fill a gap in international documentation by gathering together materials which are at present widely scattered and often difficult of access. The preparation of such a collection has been advocated by many official and unofficial bodies, and was recommended by the International Law Commission in its report of 29 July 1950. The content of this volume concerns the regime of the high seas, one of the three topics selected by the International Law Commission for early codification.